Training and Assistance for History Teachers in Implementing Inclusive Learning Models in Senior High Schools in Malaka Regency - Taneo, Malkisedek; Utomo , Susilo Setyo; Madu, Aleksius; Mali, Silvanus Jefrino; Mailani, Nino (LP2M INSURI Ponorogo, 2025)
This service activity was motivated by the lack of training and resources that support inclusive learning in schools. The aim is to equip teachers in Malacca district with the ability to implement inclusive learning models. We used the methods of planning, action, observation, evaluation and reflection. The stages began with coordination with the Malacca District Education and Culture Office, socialization to high school teachers, and program development based on situation and needs analysis. In this activity, teachers received training and mentoring and conducted inclusive learning simulations. The results show that 94.5% of teachers have adequate skills in implementing inclusive learning models in the classroom. This indicates a positive impact, where teachers become more creative in helping students according to their abilities.